Magnetic recovery reveals sequential extraction bias and supports mass-conservative assessment of lanthanum-based sediment phosphorus inactivation - Zhe Wang; Liling Wang; Chengyan Bao; Enyang Liu; Xinnuo Liu; Zezhen Pan; Feijian Mao; Xingxing Wang; Jiake Li; Deyi Wu; Qiang Xie; Zimeng Wang (Water Research, 2026)

Regulatory mechanisms of post-translational modifications on autophagic flux in neurons following ischemic stroke - Liling Yu; Wenting Zhuang; Xiong Liu; Hongqiong He; Yihao Deng; Hongyun He (Molecular Biology Reports, 2026)

Urban geological assessment for SDG 11 alignment: empirical evidence from 11 cities in Zhejiang, China - Liling Zhou; Xiaoyi Zhang; Huizhen Shen; Nina Liu; Dazheng Zhang; Haijun Bao (Tunnelling and Underground Space Technology, 2026)

Characterization and modification of chickpea husk dietary fibers: Potential applications in gummy candy and emulsion-based food products - Xiangyu Liu; Yifan Zhang; Liang Wang; Minwei Zhang; Fen Li; Huiling Yan; Kaiwen Wu; Feng Zhang; Qiao Zhang; Jun Liu; Chunlan Zhang; Liling Wang; et al. (Food Hydrocolloids, 2026)

Metabolic division of labor drives synergistic production of biomass, lipid and α-tocopherol in Euglena gracilis–Chlorella pyrenoidosa co-cultures - Zhen Wang; Qisheng Tian; Liling Fu; Xiaofan Xing; Wei Liu; Changhong Liu; Lei Zheng (Bioresource Technology, 2026)

Engineering Agriophyllum squarrosum starch-butyric acid complexes with functional properties via ionic liquids-ultrasonication synergy - Shaopan Cao; Yuxin Yang; Yongye Wu; Yang Hu; Jie Zhang; Shilong Cheng; Si Wu; Yang Liu; Liling Zhang; Ling Jiang (Food Research International, 2026)

Caffeic acid-grafted high-amylose maize starch for self-stabilizing emulsion gels: efficient encapsulation and protection of pterostilbene - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Food Chemistry, 2026)

Antimony exposure promotes cardiac fibrosis via lactate-mediated cardiomyocyte-fibroblast crosstalk: A novel Sirt1-glycolysis axis - Xin Li; Zhenzhen Dai; Xiaoyong Ren; Hao Zhao; Lirong Chan; Ruotong Wu; Xinyi Xiao; Qiao Liu; Liling Su (Journal of Environmental Sciences, 2026)

Coactive adaptation to combined drought and UV-B stress in highland barley (qingke) through hormonal and nutrient crosstalk - Noman Shoaib; Liling Liu; Nishbah Mughal; Xiaoyun Bai; Fakhar Zaman; Yan Pan; Juan Zhang; Junjie Pan; Xiaogang Wu; Xiaoming Sun; Lin Zhang; Kaiwen Pan (Plant and Soil, 2026)

A multi-dimensional modified deep learning framework for predicting potential creep-type landslides based on geological data - Yue Liu; Peihua Xu; Chen Cao; Liling Jin; Bo Han; Rongchen Ma; Chensi Li (Earth Science Informatics, 2026)

Correction to: Long-Term Monochromatic Light Exposure Does Not Alter Modular Chromatic Representation in the Visual Cortex of Rhesus Monkeys - Wenqing Zhu; Ye Liu; Xiaoxiao Chen; Liling Qian; Wei Wang; Leilei Zou; Yiliang Lu; Rui Liu (Neuroscience Bulletin, 2026)

Concurrent biodegradation of tylosin and tilmicosin by a novel Paracoccus versutus 4-B-2 - Zhengyan Chen; Anqi Liu; Junzhe Cui; Chunhui Liu; Huijuan Li; Ziyi Quan; Yaxu Liu; Xiao Guo; Xiaoyu Wang; Liling Fan; Bo Wang (Journal of Hazardous Materials, 2026)

A novel Pickering emulsion stabilized solely by n-butyric acid-modified high-amylose corn starch for resveratrol delivery - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Qisheng Tian; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Carbohydrate Polymers, 2026)

Towards low-carbon zinc extraction from zinc-containing electric arc furnace dust: A review of pyrometallurgical and hydrometallurgical routes - Yuqian Liu; Haichuan Li; Liling Jin; Dongdong Zhou; Shiyuan Liu (Journal of Environmental Chemical Engineering, 2026)

Long-Term Monochromatic Light Exposure Does Not Alter Modular Chromatic Representation in the Visual Cortex of Rhesus Monkeys - Wenqing Zhu; Ye Liu; Xiaoxiao Chen; Liling Qian; Wei Wang; Leilei Zou; Yiliang Lu; Rui Liu (Neuroscience Bulletin, 2026)

Unraveling the Low Residual Mechanism of Polycyclic Aromatic Hydrocarbons in Rice Grains Driven by Low Moisture Regulation: Microbial Mediated Health Effects - Zhenhua Zhao; Xiaorou Wang; Yueli Liu; liling Xia; Zhirui Qin; Jingjing Cao; Harry Toland (Journal of Soil Science and Plant Nutrition, 2026)

Beyond Single Stressors: Integrated Physiological and Transcriptomic Responses of Argopecten irradians Exposed to Polystyrene and Toxic Dinoflagellates - Weijia Song; Jianguo Ding; Liling Guan; Jie Ma; Huixuan Liu; Hongli Zhang; Yangjun Chen; Kaiqin Jiang (Oceans, 2026)
Toxic dinoflagellate blooms and microplastics are widespread coastal pollutants. In this study, the scallop, Argopecten irradians, was selected as an experimental organism to systematically investigate the single and combined toxic effects of polystyrene (PS) and the toxic dinoflagellate, Alexandrium pacificum. The results showed that both PS and algal cells could be ingested by A. irradians. The survival rate of A. irradians remained above 90% in both the single and combined treatment groups, indicating that 1 mg/L PS and 1500 cells/mL A. pacificum cells did not pose a serious threat to scallop survival in the short term. However, CAT, SOD, and GSH-ST activities, as well as MDA content, were all elevated in the combined treatment group. Transcriptomic analysis further revealed that A. pacificum primarily affected immune-related pathways, whereas PS might interfere with endocrine function through the release of additives. Combined exposure to PS and A. pacificum induced more complex synergistic effects, reflected in the metabolic stress of exogenous substances, and the disruption of developmental and homeostasis regulatory pathways. This study provides important theoretical support for assessing the threats posed by composite coastal pollution to aquaculture and marine ecological security.

A high-performance direct biomass fuel cell utilizing red bean shell as fuel - Guangkai Lu; Boyuan Liu; Liling Long; Yundong Qian; Xiaoyuan Zeng; Senran Hao; Weizi Cai; Jie Xiao (Fuel, 2026)

Corrigendum to “sulfated hyaluronic acid/collagen-based biomimetic hybrid nanofiber skin for diabetic wound healing: Development and preliminary evaluation” [carbohydrate polymers, volume 334, 15 June 2024, 122025] - Yuanmeng Zhou; Weibin Jia; Jiexue Bi; Meng Liu; Liling Liu; Hang Zhou; Guofeng Gu; Zonggang Chen (Carbohydrate Polymers, 2026)

Ontogenetic niche segregation and its implications for mercury levels in Japanese anchovy from the high seas of the northwestern Pacific Ocean as revealed by fatty acid analysis - Long Chen; Zhenfang Zhao; Guanyu Hu; Liling Zhang; Bilin Liu; Xinjun Chen (Journal of Fish Biology, 2025)
Japanese anchovy ( Engraulis japonicus ) is a small pelagic fish that is frequently targeted by commercial fisheries. Japanese anchovy plays a crucial role as a vital link between primary and higher‐order consumers. The elemental mercury in Japanese anchovy muscles easily bioaccumulates and is transmitted to top predators. We investigated the variation in the diets and mercury accumulation of Japanese anchovy in the high seas of the northwestern Pacific Ocean. We measured the amounts of mercury and fatty acids in the muscles of 149 Japanese anchovy specimens that were obtained from the open seas of the northwestern Pacific Ocean (39°2′ N ~ 42°30′ N, 154°02′ E ~ 161°29′ E) between June and July 2021. The results revealed that the monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA) contents significantly decreased and then increased with the growth of Japanese anchovy ( p

Assessment of potentially toxic elements (PTEs) in surface and groundwater of volcanic and granite regions of Hainan Island, China: Pollution status, sources, and health risk evaluation - Jianzhou Yang; Yong Li; Shengyue Liang; Min Zhang; Jingjing Gong; Yufang Li; Qiankun Yan; Xiaohui Sun; Zuyang Xu; Xueju Liu; Shuqi Hu; Jianweng Gao; et al. (Environmental Geochemistry and Health, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Passion fruit peel pectin improves glucose and lipid metabolism in high-fat diet-induced obesity through gut microbiota and insulin sensitivity regulation - Ying Ju; Liling Huang; Hailing Luo; Yongcai Huang; Xianya Huang; Ge Chen; Jie Gui; Shengli Lin; Xuzhou Liu; Liu Yang (Food Bioscience, 2025)

Analysis of the molecular karyotype of Kengyilia grandiglumis on the Qinghai-Tibet Plateau via sequential FISH and GISH - Ruijuan Liu; Liling Jiang; Yijun Zhong; Yue Wu; Demei Liu; Wenjie Chen (Genetic Resources and Crop Evolution, 2025)

Study on the effect of heat treatment process on the quality characteristics of soybean-Citri Reticulatae Pericarpium (CRP) based yogurt and related mechanisms - Juan Zhang; Yue Long; Yanpeng Zhang; Liling Lu; Chenxu Liu; Wei Xu; Zhixiong Hu; Chun Hu (Food Hydrocolloids, 2025)

Unraveling microbial assembly and co-occurrence relationship at seasonal and vertical scales in an aged organic-contaminated site - Zhirui Qin; Zhenhua Zhao; Liling Xia; Jiayuan Liu; Xuan Li; Aiwei Zhang; Yue Wang; Jingwei Wang (International Biodeterioration & Biodegradation, 2025)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

A multiplex RT‑PCR detection system for pepper co-infection by three potyviruses - Tiyuan Xia; Liling Mo; Xinyang Chen; Wang Wang; Pengyu Liu; Xingmei Tao; Xuan Yi; Zuqin Qiao; Yongfu Zhang; Xiaoqin Li (Journal of General Plant Pathology, 2025)

Climate change and human activities drive the warm-season rooftop solar photovoltaic potential in the Chinese Chengdu-Chongqing urban agglomeration - Yilin Li; Lijun Liu; Tianyu Zhang; Youjia Liang; Zhenghong Chen; Liling Chu; Chao He (Sustainable Cities and Society, 2025)

Legumes reduce the effects of salt stress on co-existing grass - Liling Liu; Ziyan Chen; Xiaomei Gou; Lingcao Hou; Chenglong Liang; Huan Jiao; Weibo Kong; Liping Qiu; Xiang Wang; Xiaorong Wei (Journal of Environmental Management, 2025)

Effects of diet and habitat on Hg levels in Japanese anchovy in the high seas of the northwestern Pacific Ocean - Long Chen; Guanyu Hu; Zhenfang Zhao; Bilin Liu; Xinjun Chen; Liling Zhang (Marine Pollution Bulletin, 2024)

Unveiling the dynamics of dry-and-humid, day-and-night, and compound heat waves across 209 Cities in China during 1974–2021 - Lijun Liu; Liling Chu; Youjia Liang; Jiangang Li; Miao Yu; Chao He (Urban Climate, 2024)

Synergistic reduction of air pollutants and carbon dioxide emissions in Shanxi Province, China from 2013 to 2020 - LiLing Wu; Shida Sun; Gaige Zhang; Zimu Jia; Yuyun Liu; Chenxi Xu; Mengjie Guo; Luyao Zhang; Cilan Cai; Runcao Zhang; Jialin Zheng; Wenjie He; et al. (Science of The Total Environment, 2024)

Polystyrene microplastics trigger testosterone decline via GPX1 - Jiayuan Qu; Liling Wu; Li Mou; Changjiang Liu (Science of The Total Environment, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Protective Effect of CXCR7 Against Hypoxia/Reoxygenation Injury in Renal Tubular Epithelial Cells - Ping Meng; Chunli Liu; Jingchun Li; Ping Fang; Liling Chen (Cell Biochemistry and Biophysics, 2024)
Acute kidney injury (AKI) is a multifactorial syndrome with complex pathophysiology and prognosis. Ischaemia‒reperfusion injury (IRI) is a major cause of induced AKI. The aim of this study was to investigate the effect of upregulated CXCR7 expression on renal tubular epithelial cell apoptosis induced by hypoxia/reoxygenation (H/R). HK-2 cells were divided into three groups: control group (pcDNA3.1), hypoxia/reoxygenation + pcDNA3.1 group (H/R+pcDNA3.1) and CXCR7 overexpression + hypoxia/reoxygenation group (H/R+ Flag-CXCR7). Protein levels of renal tubular epithelial cell injury-, apoptosis- and autophagy-related markers were assessed by qRT‒PCR, Western blotting, flow cytometry (FCM), immunofluorescence and transmission electron microscopy (TEM). In addition, HK-2 cells were treated with the autophagy inhibitor 3-MA and divided into 3 groups: control group, 3-MA + pcDNA3.1 group, and 3-MA + Flag-CXCR7 group. Changes in autophagy and apoptosis in renal tubule epithelial cells were assessed by Western blotting and FCM. Compared with those in the control group, the protein and mRNA expression levels of CXCR7 in HK-2 cells were significantly lower under H/R conditions. Under H/R conditions, CXCR7 overexpression in HK-2 cells significantly downregulated the expression of NGAL. Moreover, CXCR7 overexpression significantly decreased H/R-induced cleaved PARP-1 and cleaved Caspase 3 levels, increased the level of the antiapoptotic protein BCL-2 and the autophagy-related molecules ATG5 and LC3B II, and significantly inhibited the expression of P62. Autophagy flow and TEM also showed that CXCR7 significantly promoted autophagy. CXCR7 significantly alleviated the 3-MA-induced inhibition of autophagy and increase in apoptosis. Upregulated CXCR7 expression can inhibit renal tubular epithelial cell apoptosis and damage by regulating autophagy. In conclusion, CXCR7 is a promising target for the prevention and/or treatment of AKI.

Correlation between urinary rare earth elements and liver function in a Zhuang population aged 35–74 years in Nanning - Xingxi Luo; Liling Wei; Shun Liu; Kaili Wu; Dongping Huang; Suyang Xiao; Erna Guo; Lei Lei; Xiaoqiang Qiu; Xiaoyun Zeng (Journal of Trace Elements in Medicine and Biology, 2024)

First report of pod pepper vein yellows virus infecting Solanum nigrum L. in China - Yongfu Zhang; Pengyu Liu; Liling Mo; Xinyang Chen; Wang Wang; Xingmei Tao; Xiaoqin Li (Journal of Plant Pathology, 2024)

Sulfated hyaluronic acid/collagen-based biomimetic hybrid nanofiber skin for diabetic wound healing: Development and preliminary evaluation - Yuanmeng Zhou; Weibin Jia; Jiexue Bi; Meng Liu; Liling Liu; Hang Zhou; Guofeng Gu; Zonggang Chen (Carbohydrate Polymers, 2024)

NLRC3 attenuates osteoclastogenesis by limiting TNFα+ Th17 cell response in osteoporosis - Lingyan Ren; Guangjun Liu; Yun Bai; Liling Gu; Yuan Wang; Li Sun (Journal of Molecular Medicine, 2024)
NOD-like receptor family CARD domain containing 3 (NLRC3) is the intracellular protein belonging to NLR (NOD-like receptor) family. NLRC3 can negatively regulate inflammatory signal transduction pathways within the adaptive and innate immunocytes. However, studies need to elucidate the biological role of NLRC3 in bone remodeling. Herein, our study proved that NLRC3 prevents bone loss by inhibiting TNFα + Th17 cell responses. In osteoporosis, NLRC3 attenuated TNFα + Th17 cell accumulation in the bone marrow. However, osteoporosis (OP) development was aggravated without affecting bone marrow macrophage (BMM) osteoclastogenesis in NLRC3-deficient ovariectomized (OVX) mice. In this study, we transferred the wild-type and NLRC3 −/− CD4 + cells into Rag1 −/− mice. Consequently, we evidenced the effects of NLRC3 in CD4 + T cells on inhibiting the accumulation of TNFα + Th17 cells, thus restricting bone loss in the OVX mice. Simultaneously, NLRC3 −/− CD4 + T cells promoted the recruitment of osteoclast precursors and inflammatory monocytes into the OVX mouse bone marrow. Mechanism-wise, NLRC3 reduced the secretion of TNFα + Th17 cells of RANKL, MIP1α, and MCP1, depending on the T cells. In addition, NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. Collectively, this study appreciated the effect of NLRC3 on modulating bone mass via adaptive immunity depending on CD4 + cells. According to findings of this study, NLRC3 may be the candidate anti-OP therapeutic target. Key messages NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. NLRC3 may be the candidate anti-OP therapeutic target.

Long-term exposure to fine particulate matter constituents in relation to chronic kidney disease: evidence from a large population-based study in China - Yucen Dai; Jianzhong Yin; Sicheng Li; Jiawei Li; Xinyu Han; Quzong Deji; Ciren Pengcuo; Leilei Liu; Zhimiao Yu; Liling Chen; Linshen Xie; Bing Guo; et al. (Environmental Geochemistry and Health, 2024)

Invigorating active sites for amorphous/crystalline heterophased co-based oxyhydroxide/tungstate toward enhanced electrocatalytic oxygen evolution: Trimetallic codoping-achieved synergistic regulation - Jiejie Feng; Jianting Liu; Changshun Chu; Liling Wei; Huayi Li; Jianquan Shen (Chemical Engineering Journal, 2024)

Effects of intracellular Ca2+ on developmental potential and ultrastructure of cryopreserved-warmed oocyte in mouse - Junping Cheng; Xiaoli Wang; Chan Luo; Xianbao Mao; Jie Qin; Yan Chi; Bing He; Yanrong Hao; Xiangli Niu; Ben Huang; Liling Liu (Cryobiology, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

In vivo tracing of triazole pesticides in Chinese cabbage via a novel solid-phase microextraction fiber - Yingming Duan; Yiquan Huang; Liling Huang; Zhangmin Xiang; Jian Liu; Shuqin Liu; Zhuo Chen (Food Control, 2024)

CMTM 6 promotes the development of thyroid cancer by inhibiting NIS activity through activating the MAPK signaling pathway - Xin Chen; Hao Shen; Huifang Liu; Liling Tan; Nuobei Zhang (Functional & Integrative Genomics, 2024)

Combined microbe-plant remediation of cadmium in saline-alkali soil assisted by fungal mycelium-derived biochar - Zirun Zhao; Lin Liu; Ying Sun; Liling Xie; Shuo Liu; Mingchun Li; Qilin Yu (Environmental Research, 2024)

Physical, chemical, and rheological properties of konjac glucomannan phosphate ester - Liling Deng; Yongbo Peng; Yan Li; Geng Zhong; Dan Liu; Zhaojing Zhu (Journal of Food Engineering, 2023)

Association Between Wnt Target Genes and Cortical Volumes in Alzheimer’s Disease - Liling Dong; Bo Hou; Caiyan Liu; Chenhui Mao; Xinying Huang; Li Shang; Shanshan Chu; Bin Peng; Liying Cui; Feng Feng; Jing Gao (Journal of Molecular Neuroscience, 2023)
The disproportionate cortical atrophy is an established biomarker for the pathophysiological process of Alzheimer’s disease (AD). However, the genetic basis underlying the cortical atrophy remains poorly defined. Herein, we aim to illustrate the effect of the Wnt target genes on the cortical volumes of AD patients. 82 sporadic AD patients were recruited. All the subjects had history survey, blood biochemical examination, cognitive assessment, MRI morphometry and whole exome sequencing. This report focused on 84 common variants (minor allele frequency > 0.01) of 32 Wnt target genes, including the APC , DAAM1 , DACT1 , DISC1 , LATS2 , TLR2 , WDR61 , and the AXIN , DVL , FZD , LRP , TCF/LEF , WNT family genes. The Wnt target genes showed asymmetric effects on the cortical volumes of AD patients. The right temporal/parietal/occipital cortices were more affected than left temporal/parietal/occipital cortices. Nevertheless, the reverse applied to the frontal cortex. The DACT1 affected the cortical thickness most, followed by the TCF3 and APC . The DACT1 rs698025-GG genotype displayed greater right temporal pole and left medial orbito-frontal gyrus than rs698025-GA genotype (2.4 ± 0.4 vs. 2.0 ± 0.6, P = 0.005; 5.2 ± 0.6 vs. 5.0 ± 0.6, P = 0.001). The brain region most influenced by the Wnt target genes was the right calcarine cortex. In conclusion, the common variants of the Wnt target genes exert asymmetric effects on the cortical volumes of AD patients. The Wnt signaling pathway may play a role in the cortical atrophy of AD patients.

Evaluating the contribution of climate change and urbanization to the reversal in maximum surface wind speed decline: Case study in the Yangtze River Economic Belt, China - Lijun Liu; Youjia Liang; Chao He; Bin Li; Liling Chu; Jiangang Li (Urban Climate, 2023)

Optimizing directional recovery of high-bioavailable phosphorus from human manure: Molecular-level understanding and assessment of application potential - Yao Xu; Nan Li; Libin Yang; Tongcai Liu; Shaoze Xiao; Liling Zhou; Dapeng Li; Jiabin Chen; Yalei Zhang; Xuefei Zhou (Water Research, 2023)

Significant roles of core prokaryotic microbiota across soil profiles in an organic contaminated site: Insight into microbial assemblage, co-occurrence patterns, and potentially key ecological functions - Zhirui Qin; Zhenhua Zhao; Liling Xia; Guangwen Yu; Aihua Miao; Yuhong Liu (Environmental Research, 2023)

Temporal Variations of Water Quality and Pollution Source Structures Over 15 Years Reflect Effects of Water Pollution Control in the Upper Tuojiang River Basin, China - Xiaocong Liu; Hongjin Tong; Qiang Chen; Yao Wei; Zhuang Liu; Liling Zhang; Jingyi Zhang (Water, Air, & Soil Pollution, 2023)

Adverse effects of triclosan exposure on health and potential molecular mechanisms - Xuhui Chen; Li Mou; Jiayuan Qu; Liling Wu; Changjiang Liu (Science of The Total Environment, 2023)

NCX2 Regulates Intracellular Calcium Homeostasis and Translocation of HIF-1α into the Nucleus to Inhibit Glioma Invasion - Hongyuan Liu; Ju Yu; Liling Yang; Pengcheng He; Zongping Li (Biochemical Genetics, 2023)
Glioma is the most common tumor of the central nervous system, and its poor prognosis can be linked to hypoxia and gene inactivation. Na + /Ca 2+ exchanger 2 (NCX2) is expressed only in the normal brain and not in other tissues or glioma. We constructed a hypoxic microenvironment to more accurately understand the effect of NCX2 in glioma. Our previous experiments confirmed that NCX2 inhibited the growth of U87 cells in nude mice, indicating that NCX2 is a potential tumor suppressor gene. Malignant tumor cells are often exposed to an anoxic environment. To more accurately understand the effect of NCX2 in glioma, we constructed a hypoxic microenvironment. To detect the localization of NCX2 in transfected U87 cells, immunofluorescence was used. We tested the function of NCX2 in glioma, i.e., how it contributes to the cytosolic Ca 2+ homeostasis by X-Rhod-1. We tested the cell proliferation of NCX2 in glioma in hypoxic using Cell counting kit-8 (CCK8). Cell migration and invasion were evaluated in 24-well transwell matrigel-coated or non-matrigel-coated in hypoxia. NCX2 promoted the proliferation of U87 cells in the hypoxic microenvironment. It inhibited the invasion and migration abilities of U87 cells. We demonstrated that NCX2 was located on the cell membrane and that it reduced intracellular Ca 2+ levels and reactivated P53 and PTEN. We further demonstrated that NCX2 impaired cell invasion through the HIF-1α pathway in glioma. The results indicated that NCX2 plays a key role in glioma formation and tumor invasion functionality.

Continued evolution of the Eurasian avian-like H1N1 swine influenza viruses in China - Fei Meng; Yan Chen; Zuchen Song; Qiu Zhong; Yijie Zhang; Chuanling Qiao; Cheng Yan; Huihui Kong; Liling Liu; Chengjun Li; Huanliang Yang; Hualan Chen (Science China Life Sciences, 2023)

The ecological response and distribution characteristics of microorganisms and polycyclic aromatic hydrocarbons in a retired coal gas plant post-thermal remediation site - Zhenhua Zhao; Barry Mody Oury; Liling Xia; Zhirui Qin; Xiangyu Pan; Jichan Qian; Fangzhou Luo; Yong Wu; Luqi Liu; Wei Wang (Science of The Total Environment, 2023)

Afforestation can lower microbial diversity and functionality in deep soil layers in a semiarid region - Weibo Kong; Xiaorong Wei; Yonghong Wu; Mingan Shao; Qian Zhang; Michael J. Sadowsky; Satoshi Ishii; Peter B. Reich; Gehong Wei; Shuo Jiao; Liping Qiu; Liling Liu (Global Change Biology, 2022)
Afforestation is an effective approach to rehabilitate degraded ecosystems, but often depletes deep soil moisture. Presently, it is not known how an afforestation‐induced decrease in moisture affects soil microbial community and functionality, hindering our ability to understand the sustainability of the rehabilitated ecosystems. To address this issue, we examined the impacts of 20 years of afforestation on soil bacterial community, co‐occurrence pattern, and functionalities along vertical profile (0–500 cm depth) in a semiarid region of China's Loess Plateau. We showed that the effects of afforestation with a deep‐rooted legume tree on cropland were greater in deep than that of in top layers, resulting in decreased bacterial beta diversity, more responsive bacterial taxa and functional groups, increased homogeneous selection, and decreased network robustness in deep soils (120–500 cm). Organic carbon and nitrogen decomposition rates and multifunctionality also significantly decreased by afforestation, and microbial carbon limitation significantly increased in deep soils. Moreover, changes in microbial community and functionality in deep layer was largely related to changes in soil moisture. Such negative impacts on deep soils should be fully considered for assessing afforestation's eco‐environment effects and for the sustainability of ecosystems because deep soils have important influence on forest ecosystems in semiarid and arid climates.

Tumour suppression by Chinese cordyceps extract via antiangiogenic activity - Wenjia Li; Jing Li; Xuefeng Hu; Linghua Xu; Xiaoyu Liu; Zhengming Qian; Liling Jin; Yimin Zhang; Jiangchun Wei; Xingzhong Liu (Mycological Progress, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

A Systematic Approach for Liposome and Lipodisk Preclinical Formulation Development by Microfluidic Technology - Elizabeth S. Levy; Jesse Yu; Alberto Estevez; Jialin Mao; Liling Liu; Elizabeth Torres; Dennis Leung; Chun-Wan Yen (The AAPS Journal, 2021)

Temperature changes between neighboring days and childhood asthma: a seasonal analysis in Shanghai, China - Xiaoning Lei; Lijuan Liu; Renjie Chen; Cong Liu; Jianguo Hong; Lanfang Cao; Yanming Lu; Xiaoyan Dong; Xinchang Chen; Xiangwei Qiu; Min Xia; Bo Ding; et al. (International Journal of Biometeorology, 2021)

Phenotype Heterogeneity and Genotype Correlation of MAPT Mutations in a Chinese PUMCH Cohort - Chenhui Mao; Liling Dong; Jie Li; Xinying Huang; Dan Lei; Jie Wang; Shanshan Chu; Caiyan Liu; Bin Peng; Liying Cui; Jing Gao (Journal of Molecular Neuroscience, 2021)

Transcriptome profiling provides insights into the fruit color development of wild Lycium ruthenicum Murr. from Qinghai–Tibet Plateau - Yinyan Qi; Haibin Wei; Wenyi Gu; Wenjun Shi; Liling Jiang; Lei Deng; Xiaoli Liu (Protoplasma, 2021)

Influence and interaction of iron and lead on seed germination in upland rice - Liling Wang; Bentong Liu; Yanbin Wang; Yuchuan Qin; Yifeng Zhou; Hua Qian (Plant and Soil, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Glycosylation and an amino acid insertion in the head of hemagglutinin independently affect the antigenic properties of H5N1 avian influenza viruses - Chunyang Gu; Xianying Zeng; Yangming Song; Yanbing Li; Liling Liu; Yoshihiro Kawaoka; Dongming Zhao; Hualan Chen (Science China Life Sciences, 2019)

Correction to: Strategies of Drug Transporter Quantitation by LC-MS: Importance of Peptide Selection and Digestion Efficiency - Buyun Chen; Liling Liu; Hoangdung Ho; Yuan Chen; Ze Yang; Xiaorong Liang; Jian Payandeh; Brian Dean; Cornelis E. C. A. Hop; Yuzhong Deng (The AAPS Journal, 2018)

Epidemiological and genetic characteristics of the fifth avian influenza A(H7N9) wave in Suzhou, China, from October 2016 to April 2017 - Zefeng Dong; Yu Xia; Xuerong Ya; Liling Chen; Cheng Liu; Ruyan Wang; Qiang Shen (Virus Genes, 2018)

Strategies of Drug Transporter Quantitation by LC-MS: Importance of Peptide Selection and Digestion Efficiency - Buyun Chen; Liling Liu; Hoangdung Ho; Yuan Chen; Ze Yang; Xiaorong Liang; Jian Payandeh; Brian Dean; Cornelis E. C. A. Hop; Yuzhong Deng (The AAPS Journal, 2017)

Arsenic Trioxide and Icariin Show Synergistic Anti-leukemic Activity - Zhi Wang; Hong Zhang; Liling Dai; Tongguo Song; Ping Li; Yali Liu; Luning Wang (Cell Biochemistry and Biophysics, 2015)

Photocatalytic degradation of phenol with mesoporous TiO2−xBx - Leyan Xiong; Longzhen Zheng; Jingpeng Xu; Dan Zheng; Junhua Li; Xinjia Li; Juan Sun; Qiang Liu; Liling Niu; Shaoming Yang; Jian Xia (Environmental Chemistry Letters, 2011)

Nitric oxide enhances salt tolerance in maize seedlings through increasing activities of proton-pump and Na+/H+ antiport in the tonoplast - Yanyan Zhang; Liling Wang; Youliang Liu; Qun Zhang; Qiuping Wei; Wenhua Zhang (Planta, 2006)

Characterization of An Avian Influenza Virus of Subtype H7N2 Isolated from Chickens in Northern China - Yanbing Li; Chengjun Li; Liling Liu; Hongwei Wang; Chuanbin Wang; Guobing Tian; Robert G. Webster; Kangzhen Yu; Hualan Chen (Virus Genes, 2006)